Circulating let‐7 Predicts Hepatic Fibrogenesis of 12‐Month Post‐Nucleos(t)ide Analog Treatment in Patients With Hepatitis B Virus - Yi‐Shan Tsai; Po‐Cheng Liang; Yi‐Hung Lin; Tyng‐Yuan Jang; Yu‐Ju Wei; Po‐Han Chen; Jia‐Ning Hsu; Meng‐Hsuan Hsieh; Ming‐Yen Hsieh; Chih‐Wen Wang; Zu‐Yau Lin; Ming‐Lun Yeh; et al. (Kaohsiung Journal of Medical Sciences, 2025)
ABSTRACT Chronic hepatitis B virus (HBV) infection is associated with potential complications of liver cirrhosis and hepatocellular carcinoma. To date, there are no effective and noninvasive clinical markers that can predict the risk of liver fibrosis early and accurately in chronic hepatitis B (CHB) patients treated with nucleos(t)ide analogs (NAs). This study aimed to investigate the association of circulating let‐7b/c/g levels with the severity of hepatic fibrosis with a FIB‐4 index of 1.5–2.9 in CHB patients. We conducted a retrospective longitudinal study in patients with CHB after 6 months of NAs therapy to investigate whether serum let‐7b/c/g levels can be monitored as an early biomarker for liver fibrogenesis based on multivariate logistic regression analyses. We also used the hepatic stellate cell line LX‐2 treated with transforming growth factor‐β (TGF‐β) to evaluate the suppression effect of let‐7b/c/g on hepatic fibrogenesis. The study showed that circulating let‐7b/c/g could predict 12 months of antiviral treatment for HBV‐related significant fibrosis (FIB‐4 index ≥ 2.9) at baseline and was significantly negatively correlated with the FIB‐4 score. Moreover, let‐7b/c/g could directly target the TGF‐βR1–3′ untranslated region (3′ UTR) and inhibit TGF‐β induced p‐SMAD2 phosphorylation to reduce α‐smooth muscle actin levels, a fibrogenesis marker in LX‐2 cells. These results confirm that let‐7b/c/g could be a biomarker for monitoring HBV‐induced fibrogenesis.